Tinjauan dan Implementasi Terhadap Arsip Wilayah Perbatasan Negara Sebagai Wujud Penyelamatan Arsip Negara Dengan Tujuan Menjaga Keutuhan dan Kedaulatan NKRI - Br. Yohanes Arman SVD; Michael Fence Dalle; Efrida Ika Nay (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The goal to be achieved from this research is to find out the review and implementation of the state border areas as a form of saving state archives with the aim of maintaining the integrity and sovereignty of the Unitary State of the Republic of Indonesia. researching library materials or secondary data. The border area of the country is an inseparable part of the history of a nation, as a nation's historical struggle to be recognized for its existence. Therefore, the history of border areas cannot be separated from the history of the birth (rise) or end (fall) of a nation. Indonesia as an archipelagic country certainly has an interest in the border areas of the country. Verification of the territory of the Unitary State of the Republic of Indonesia (NKRI) which is vast and has land and sea borders with several countries must be supported by data and historical facts of the border area as part of the history of the Indonesian nation. As well as the management of state border area archives within the state and regional government institutions is carried out in the context of protecting and saving state archives and the form of implementation to realize the goals of organizing archives.